Optimization of SrRuO3 bottom electrodes fabricated by RF magnetron ion sputtering for new generation devices. (2021) - Sharma, Subhash; Vázquez Valerdi, Diana E.; Campos Mendoza, Raúl; Yocupicio-Gaxiola, Rosario I.; Abundiz Cisneros, Noemí; Siqueiros, J.M.; Raymond Herrera, Oscar
Abstract: Multiferroic materials show great academic and technological interest for their role in new generation devices due to the coexistence of magnetic, ferroelectric and elastic ordering. In this article the fabrication of SrRuO3 (SRO) thin films by the RF magnetron ion sputtering technique is presented where the deposition conditions, namely deposit time, substrate temperature and RF power were optimized. The growth of the SRO phase was evaluated using X-ray diffraction. The homogeneity of the films was analysed using energy dispersive X-ray spectroscopy. Film thickness and optical properties were determined by ellipsometry.